Gene Duplication, Lineage-Specific Expansion, and Subfunctionalization in the MADF-BESS Family Patterns the Drosophila Wing Hinge - Shukla, Vallari (Genetics Society of America, 2014)
Gene duplication, expansion, and subsequent diversification are features of the evolutionary process. Duplicated genes can be lost, modified, or altered to generate novel functions over evolutionary timescales. These features make gene duplication a powerful engine of evolutionary change. In this study, we explore these features in the MADF-BESS family of transcriptional regulators. In Drosophila melanogaster, the family contains 16 similar members, each containing an N-terminal, DNA-binding MADF domain and a C-terminal, protein-interacting, BESS domain. Phylogenetic analysis shows that members of the MADF-BESS family are expanded in the Drosophila lineage. Three members, which we name hinge1, hinge2, and hinge3 are required for wing development, with a critical role in the wing hinge. hinge1 is a negative regulator of Winglesss expression and interacts with core wing-hinge patterning genes such as teashirt, homothorax, and jing. Double knockdowns along with heterologous rescue experiments are used to demonstrate that members of the MADF-BESS family retain function in the wing hinge, in spite of expansion and diversification for over 40 million years. The wing hinge connects the blade to the thorax and has critical roles in fluttering during flight. MADF-BESS family genes appear to retain redundant functions to shape and form elements of the wing hinge in a robust and fail-safe manner.